Contemplation as a Way to Achieve Enlightenment in Thoughts of St. Gregory of Nyssa - Christianus Lanang Prasaja Lod (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2025)
Contemplation is a profound and important spiritual practice in the Christian tradition, especially in the thought of St. Gregory of Nyssa. This paper aims to explore the role of contemplation as a path to achieving enlightenment and mystical union with God. The method used in this paper is a qualitative method, namely the author analyzes the thoughts of Gregory of Nyssa, who emphasizes that contemplation is not only a tool to achieve inner peace, but also a means to understand divine truth, know oneself, and develop compassion for others. The results of this study are that Gregory sees contemplation as a process of self-purification that brings the soul closer to God, through a continuous spiritual journey (epectasis). Gregory's thought invites to experience a profound spiritual transformation, find meaning in relationships with God and others, and achieve inner peace in the midst of a busy and divided world.